The Effect of Dietary Education on Improving Maternal Nutritional Behavior Among Mothers of Stunted Toddlers at the Pratama Kesira Mutiara Clinic - Wilda Yunita; Dwi Ris Hasanah. S; Lili Nurmaliza; Rhina Chairani Lubis (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2026)
Proper feeding practices are essential for preventing stunting in toddlers, yet many mothers lack adequate knowledge about nutrition. Education on feeding patterns can help mothers to make wiser decisions about their children’s diets.  This study employed a single-group quasi-experimental design with a pre-test–post-test, conducted at the Pratama Kesira Mutiara Clinic between November 2024 and April 2025. The sample consisted of 43 mothers of toddlers, selected through purposive sampling technique from a population of 76 clinic visitors, who met the inclusion criteria: having healthy toddlers, being able to communicate effectively, and agreeing to participate. Dietary education served as the independent variable, while improvements in mothers' nutritional behaviour served as the dependent variable. Data were collected using structured instruments and analysed descriptively (univariate) and inferentially (bivariate) with paired t-tests for normally distributed data or Wilcoxon tests for non-normal data.  Results showed that dietary education significantly improved mothers’ feeding behaviour, shifting the majority from inappropriate practices before the intervention to appropriate practices afterward (p < 0, 05). These findings are consistent with previous evidence that dietary education enhances feeding practices and support better child nutrition. Overall, structured educational interventions delivered by health workers play a crucial role in empowering mothers and advancing sustainable stunting prevention efforts. Keywords: Education, Stunting, Toddlers, Nutrition.